Evaluation of the Anti-Tumor Activity of the Humanized Monoclonal Antibody NEO-201 in Preclinical Models of Ovarian Cancer - Zeligs, Kristen P.; Morelli, Maria Pia; David, Justin M.; Neuman, Monica; Hernandez, Lidia; Hewitt, Stephen; Ozaki, Michelle; Osei-Tutu, Akosua; Anderson, David; Andresson, Thorkell; Das, Sudipto; Lack, Justin; et al. (Frontiers in Oncology, 2020)
Purpose: Despite high initial response rates with cytoreductive surgery, conventional chemotherapy and the incorporation of biologic agents, ovarian cancer patients often relapse and die from their disease. New approaches are needed to improve patient outcomes. This study was designed to evaluate the antitumor activity of NEO-201 in preclinical models of ovarian cancer where the NEO-201 target is highly expressed. Experimental Design: Functional analysis of NEO-201 against tumor cell lines was performed by ADCC assays. Binding of NEO-201 to tumor tissues and cell lines were determined by immunohistochemistry (IHC) and flow cytometry respectively. Further characterization of NEO-201 antigen was performed by mass spectrometry. Ovarian cancer models were used to evaluate the anti-tumor activity of NEO-201 mAb in vivo. NEO-201 at a concentration of 250 g/mouse was injected intraperitoneal (IP) on day 1, 4 and 8. Human PBMCs were injected IP simultaneously as effector cells. Results: Both IHC and flow cytometry revealed that NEO-201 binds prominently to colon, pancreatic, and mucinous ovarian cancer tissue and cell lines. Immunoprecipitation of NEO-201 antigen was performed in human ovarian, colon and pancreatic cancer cell lines. From these screening the CEACAM5 and CEACAM 6 were identified as the most likely targets of NEO-201. Our results confirmed that NEO-201 binds different types of cancers, the binding is highly selective for the tumor cells without cross reactivity with the surrounding healthy tissue. Functional analysis revealed that NEO-201 mediates ADCC killing against human ovarian and colorectal carcinoma cell lines in vitro. In addition, NEO-201 inhibited tumor growth in the presence of activated human PBMCs in orthotopic mouse models of both primary and metastatic ovarian cancer. Importantly, NEO-201 prolonged survival of tumor-bearing mice. Conclusions: These data suggested that NEO-201 has an antitumor activity against tumor cells expressing its antigen. Targeting an antigen expressed in tumors but not in normal tissues allows patient selection for optimal treatment. These findings strongly indicate that NEO-201 warrants clinical testing as both a novel therapeutic and diagnostic agent for treatment of ovarian carcinomas. A first in human clinical trial evaluating NEO-201 in adults with chemo–resistant solid tumors is ongoing at the NIH clinical Center.